The Neurodevelopmental Dynamics of Multilingual Experience During Childhood: A Longitudinal Behavioral, Structural, and Functional MRI Study - Pasquale Anthony Della Rosa; Gerda Videsott; Virginia Maria Borsa; Eleonora Catricalà; Nicolò Pecco; Federica Alemanno; Matteo Canini; Andrea Falini; Rita Franceschini; Jubin Abutalebi (Brain Sciences)
Background/Objectives: A neurobiological framework of bi- or multilingual neurocognitive development must consider the following: (i) longitudinal behavioral and neural measures; (ii) brain developmental constraints across structure and function; and (iii) the development of global multilingual competence in a homogeneous social environment. In this study, we investigated whether multilingual competence yields early changes in executive attention control mechanisms and their underlying neural structures in the frontal–striatal system, such as the dorsal anterior cingulate cortex/pre-supplemental area and the left caudate. Methods: We employed longitudinal neuroimaging and functional connectivity methods in a small group of multilingual children over two years. Results: We found that the dACC/preSMA is functionally influenced by changes in multilingual competence but not yet structurally adapted, while the left caudate, in a developmental stage, is influenced, adapts, and specializes due to multilingual experience. Furthermore, increases in multilingual competence strengthen connections between the dACC/preSMA, left caudate, and other structures of the cognitive control network, such as the right inferior frontal gyrus and bilateral inferior parietal lobules. Conclusions: These findings suggest that multilingual competence impacts brain “adaptation” and “specialization” during childhood. The results may provide insights and guide future research on experience-expectant and experience-dependent brain plasticity to explain the “interaction” between multilingualism and neurodevelopment.